2023
DOI: 10.3390/ijms24065964
|View full text |Cite
|
Sign up to set email alerts
|

Chalcones and Gastrointestinal Cancers: Experimental Evidence

Abstract: Colorectal (CRC) and gastric cancers (GC) are the most common digestive tract cancers with a high incidence rate worldwide. The current treatment including surgery, chemotherapy or radiotherapy has several limitations such as drug toxicity, cancer recurrence or drug resistance and thus it is a great challenge to discover an effective and safe therapy for CRC and GC. In the last decade, numerous phytochemicals and their synthetic analogs have attracted attention due to their anticancer effect and low organ toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 266 publications
1
7
0
Order By: Relevance
“…These results could be explained by the fact that both, coumarin and chalcone, involve many anticancer mechanisms, including cell cycle arrest, ROS production and apoptosis. [31,[58][59][60] This is also in accordance with those previous reports made by Wang and colleagues [46] who showed a coumarin-chalcone hybrid which efficiently delivered to cells to induce apoptosis through the generation of intracellular ROS in a colorectal carcinoma cell line HCT116. Besides, in other study, Singh and colleagues [61] had demonstrated that a coumarin-chalcone hybrid caused cell cycle arrest at G2/M phase and induced intrinsic caspase-dependent apoptosis mediated by alterations in the cellular levels of Bcl-2 family proteins in cervical cancer cell lines (HeLa and C33A).…”
Section: Antiproliferative Effect Of Hybrid 3c On Human Colorectal Ad...supporting
confidence: 91%
“…These results could be explained by the fact that both, coumarin and chalcone, involve many anticancer mechanisms, including cell cycle arrest, ROS production and apoptosis. [31,[58][59][60] This is also in accordance with those previous reports made by Wang and colleagues [46] who showed a coumarin-chalcone hybrid which efficiently delivered to cells to induce apoptosis through the generation of intracellular ROS in a colorectal carcinoma cell line HCT116. Besides, in other study, Singh and colleagues [61] had demonstrated that a coumarin-chalcone hybrid caused cell cycle arrest at G2/M phase and induced intrinsic caspase-dependent apoptosis mediated by alterations in the cellular levels of Bcl-2 family proteins in cervical cancer cell lines (HeLa and C33A).…”
Section: Antiproliferative Effect Of Hybrid 3c On Human Colorectal Ad...supporting
confidence: 91%
“…Among the polyphenol family, flavonoids are one of the most important and vast groups of compounds with a basic skeleton comprising two benzene rings linked through a heterocyclic ring, involving over 9000 species of molecules ( Gonzalez et al., 2021 ). Many flavonoids have been shown to possess promising antimicrobial capacity against H. pylori , including kaempferol, chalcone, myricetin, taxifolin, and other compounds with proven validity ( Krzyżek et al., 2021 ; Stenger Moura et al., 2021 ; Yang et al., 2022 ; Michalkova et al., 2023 ). Flavonoids contribute to several antibacterial mechanisms, such as the inhibition of crucial enzymes for colonization, survival, and reproduction ( Asha et al., 2013 ; Steinmann et al., 2013 ; Egas et al., 2018 ), and interference with the fluidity and stability of the cytoplasmic membrane ( Tsuchiya and Iinuma, 2000 ; Yang et al., 2022 ).…”
Section: Natural Products Effects In H Pylori Erad...mentioning
confidence: 99%
“…This unique structure allows them to interact with specific molecular targets within the cancer cells. They have demonstrated significant anticancer properties, making them attractive candidates for targeted therapeutics in the fight against colon cancer [3]. This review will focus on utilizing natural chalcones and some derivatives (such as curcumin) as targeted therapeutics for colon cancer, exploring their intriguing anticancer properties and mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, one promising avenue in colon cancer treatment has emerged in the form of chalcones, a class of compounds with diverse pharmacological activities. Chalcones have garnered attention for their potential to modulate the multiple signaling pathways implicated in CRC development and progression [ 3 ]. Chalcones (except for curcumin, which may be considered a bis-chalcone derivative) are characterized by their chemical structure, which consists of two aromatic rings linked by a three-carbon α,β-unsaturated carbonyl system [ 4 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation